Effects of aeration on the synthesis of poly(3-hydroxybutyrate) from glycerol and glucose in recombinant Escherichia coli - de Almeida, Alejandra (2010)
Bioreactor cultures of Escherichia coli recombinants carrying phaBAC and phaP of Azotobacter sp. FA8 grown on glycerol under low-agitation conditions accumulated more poly(3-hydroxybutyrate) (PHB) and ethanol than at high agitation, while in glucose cultures, low agitation led to a decrease in PHB formation. Cells produced smaller amounts of acids from glycerol than from glucose. Glycerol batch cultures stirred at 125 rpm accumulated, in 24 h, 30.1% (wt/wt) PHB with a relative molecular mass of 1.9 MDa, close to that of PHB obtained using glucose. Copyright © 2010, American Society for Microbiology. All Rights Reserved.